Dining out behaviour among senior citizens in the Klang Valley, Malaysia - Ganesan, Lalitha (2019)
The growth of senior citizens globally is inevitable as the by-product of medical technology advancement, lower fertility rate, better quality of life and higher life expectancy. They are the growing market segment worldwide. Nevertheless, this age segment does not receive the attention they should as a consumer. The stereotype held about senior citizens prevents most marketers from even trying to attract this increasingly profitable group. Food consumption trend is not the same for all age group and little is known about the restaurant choice behaviour of the senior citizens. To fill the gap in the study, this research will focus on identifying the factors, barriers and demographic characteristic of senior citizens that influence them to visit a restaurant. Qualitative approach was used in this study. A total of 15 informants aged 55 and above were chosen from Klang Valley using the purposive sampling method. Semi-structured interviews were conducted and the whole interview were recorded using a voice recorder or by pen-and-paper method. The obtained recordings were then transcribed, translated, coded, and analysed. Atlas.ti software (version 7) was used in coding of the themes with the help of a codebook created from previous literatures and based on collected data. Factors identified in the study were ageing, life’s perspective, socializing, food, service, location, price and discounts, and recommendation whereas barriers identified in this research were cleanliness, service, ageing, life’s perspective and food. Some of the factors are both a reason and barrier to visit a restaurant. The demographic characteristic that influence the behaviour were education level, income and employment status and culture and religion. Recognising the factors and barriers and improvising the restaurant marketing strategy based on it is expected to be beneficial.